Tinjauan Yuridis Pelaksanaan Jaminan Sosial Tenaga Kerja di PT. Mitratani Dua Tujuh Kabupaten Jember - Sholeh, Sholeh; Hariandja, Tioma R.; Nofitasari, Solehari; Winiari Wahyuningtyas, Yuli (WELFARE STATE Jurnal Hukum, 2023)
Every worker has rights and obligations that must be fulfilled and vice versa for the company. Workers as executors must have their rights guaranteed through social insurance. In the Amendment to Article 28 H of the 1945 Constitution paragraph (3) stipulates that everyone has the right to obtain social insurance for their survival, including workers. Implementation of the workers' social insurance program at PT. Mitratani Dua Seven Jember Regency is divided into 2 (two) type: first type is Permanent Employees and Contract Employess (PKWT) and second type is Seasonal Employees. Permanent employees and PKWT are registered in 4 (four) insurance programs are: Old Age Benefits (JHT), Work Accident Benefits (JKK), Death Benefits (JKM) and Pension Benefits (JP), while seasonal employees are registered in 3 (three) insurance programs, namely Old Age Benefits ( JHT), work accident insurance (JKK), death insurance (JKM). Obstacles in the implementation of the Employment BPJS program for seasonal workers are related to the very high entry and exit of workers because they cannot adapt to the work environment.